Bookclubbed to death [large type] - Burns, V. M., 1964- (Burns, V. M., 1964- Mystery bookshop mystery., 2023)
"After the local library in North Harbor, Michigan, is flooded in a storm, Sam offers her bookstore as a new venue for the Mystery Mavens Book Club. Unfortunately, she immediately runs afoul of the club leader, Delia Marshall. But the next morning, Sam opens her shop to find the woman dead on the floor, bashed with a heavy tome: The Complete Works of Agatha Christie. A pair of ambitious cops suspect Sam. When she gathers Nano Jo and their friends from the Shady Acres Retirement Village to review the case, they discover every one of the Mavens had a motive. Sam must find out who clubbed Delia before a judge throws the book at her"--